2017
DOI: 10.1002/jsfa.8538
|View full text |Cite
|
Sign up to set email alerts
|

Odors generated from the Maillard reaction affect autonomic nervous activity and decrease blood pressure through the olfactory system

Abstract: It is indicated that DMHF affects blood pressure through the olfactory system, and the mechanism for the effect of DMHF on blood pressure involves the autonomic nervous system. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…We previously revealed that the inhalation of DMHF changed autonomic nerve activity and decreased SBP (Zhou et al., 2018), and these changes in autonomic nerve activity were closely related to physiological activities, including appetite. In the present study, the inhalation of DMHF by rats promoted appetite during 6 weeks of feeding.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…We previously revealed that the inhalation of DMHF changed autonomic nerve activity and decreased SBP (Zhou et al., 2018), and these changes in autonomic nerve activity were closely related to physiological activities, including appetite. In the present study, the inhalation of DMHF by rats promoted appetite during 6 weeks of feeding.…”
Section: Resultsmentioning
confidence: 96%
“…DMHF (purity >98%, Kanto Chemical Co. Tokyo, Japan) was diluted with distilled water to 5.7 mg/L. DMHF concentration (5.7 mg/L) used in this study was adopted our previous study (Zhou et al., 2018). Rats were exposed to cotton (5 cm × 5 cm × 1.5 cm) soaked in 15 mL of distilled water (control) or 15 mL of DMHF solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, DMHF with high FD factor and OAV would be a key responsible agent for the physiological activities. We previously found that the inhalation of DMHF at 5.7 ppm to Wistar rats decreased SBP 32 and promoted appetite 45 via parasympathetic nerve activity. As shown in Fig.…”
Section: Discussionmentioning
confidence: 95%
“…We have paid particular attention to physiological activities of DMHF through inhalation 22,26,[30][31][32][33] . DMHF is present in natural fruits (e.g., strawberries and pineapple) 34,35 and processed foods [36][37][38] .…”
Section: Discussionmentioning
confidence: 99%